Holocaust consciousness and Cold War violence in Latin America - Tarica, Estelle (SUNY Series in Latin American and Iberian Thought and Culture Ser., 2022)
Examines how community leaders, writers, and political activists facing state repression in Latin America have drawn on and debated the validity of Holocaust terms to describe human rights atrocities in their own countries.